Identification and characterization of two types of triacylglycerol lipase genes from Neocaridina denticulata sinensis. Issue 131 (December 2022) - Liang, Meiling; Ma, Liya; Li, Xin; Feng, Dandan; Zhang, Jiquan; Sun, Yuying
Abstract: Triacylglycerol lipases (TGLs) can catalyze the hydrolysis reaction of triacylglycerol serving multiple functions in most organisms. Based on the genomic and transcriptomic databases of Neocaridina denticulata sinensis, two TGL genes from N. denticulata sinensis designated NdTGL1 and NdTGL2 were identified and characterized. NdTGL1 showed the highest expression in the stomach, followed by the testis and hepatopancreas, and NdTGL2 exhibited the maximum expression in the hepatopancreas, followed by the stomach and heart. Under the stimulation of copper ion, the expression of NdTGL1 peaked at 12 h and the expression of NdTGL2 elevated significantly at 24 h after stimulation (P < 0.05). It is speculated that NdTGLs may play an important role in the stress response of N. denticulata sinensis . Challenged with Vibrio parahaemolyticus, the expression profiles of NdTGL1 and NdTGL2 in the hepatopancreas was different, which indicates that the immune response of the V. parahaemolyticus challenge might lead to changes in triglyceride metabolism. The recombinant NdTGL (recNdTGL1 and recNdTGL2) were obtained and the enzymatic characterization of recNdTGL1 and recNdTGL2 were determined. The common maximum activity and stability of the recNdTGL1 and recNdTGL2 were observed at 45 °C and 10 °C, respectively. Both recNdTGL1 and recNdTGL2 exhibited the highest activity at pH 10.0. Furthermore, the recNdTGL1 and recNdTGL2 displayed the maximum stability at pH 5.0 and pH 8.0, respectively. In presence of different metal ions, the enzyme activity of recNdTGL1 and recNdTGL2 were inhibited by Cu 2+ and Zn 2+, and decreased by about 25%. Studies on the triacylglycerol lipases of N. denticulata sinensis provide theoretical support for studies related to fat metabolism in crustaceans and studies on response mechanism of digestive enzymes to microbial pathogens. Graphical abstract: Image 1 Highlights: Two TGL genes of N. denticulata sinensis were firstly identified and charactered. NdTGL1 was highly expressed in stomach and NdTGL2 had the maximum expression in hepatopancreas. The expression levels of NdTGLs were elevated after the stimulation of Cu 2+ and changed under the V. parahaemolyticus challenge. The recNdTGLs exhibited high activity in alkaline pH and displayed high stability at low temperature.